Concomitant pulmonary valve replacement with intracardiac repair for adult tetralogy of fallot - Anil Jain; Suresh Kumar Rajan; Kartik Patel; Pankaj Garg; Vishal Agrawal; Deepti Kakkar; Trushar Gajjar; Amit Mishra; Sanjay Patel; Chirag Doshi (Wolters Kluwer Medknow Publications, 2021)
Objectives : Adult patients undergoing tetralogy of Fallot (TOF) repair have a higher risk of mortality compared to pediatric patients. Pulmonary regurgitation (PR) further predisposes these patients to heart failure, arrhythmias, and sudden death. Pulmonary valve replacement (PVR) may improve the symptoms in these patients but, fails to reverse the other deleterious effects. Aim of our study was to evaluate the effect of concomitant PVR with TOF repair on right ventricular (RV) parameters, cardiopulmonary exercise capacity, and bioprosthetic valve durability at mid-term. Materials and Methods: Between January 2013 and August 2018, 37 adolescents and adults with TOF who had hypoplastic pulmonary annulus underwent concomitant TOF repair with PVR at our institute. We retrospectively collected the data from the hospital records including follow-up. Results : Mean age of the patients was 18.48 ± 7.53 years. Bioprosthetic valve size ranged from 19 mm to 25 mm. There was no early or late mortality. No patient had developed significant perioperative complications. At a mean follow-up of 53.3 ± 16.4 months, there was no significant change in mean QRS duration, RV function, RV end-systolic and end-diastolic dimensions, RV myocardial performance index, and functional status (including NYHA class and 6-min walk test) compared to at-discharge values. Four patients developed prosthetic valve degeneration with mild PR and without significant increase in gradient. Conclusion : Concomitant PVR with TOF repair in adult provides excellent mid-term outcome, with a minimal rate of pulmonary valve degeneration. It not only eases the early postoperative course but also preserves the RV function as well as functional status at mid-term.